Comparison of different heterogeneous catalysts for the estolides synthesis from oleic acid - Nordin N.A.M.; Adnan N.F.; Hamzah N.; Isahak W.N.R.W.; Ayatillah A.; Salimon J.; Yarmo M.A.; Kamaruddin R.A. (2023)
Different catalysts, namely various loading of perchloric acid on various supports; HClO4/silica (SiO2), HClO4/silica gel (SG) and HClO4/alumina (Al2O3) were tested for the direct addition reaction of oleic acid (OA) to form estolide compounds. The reactions were carried out under vacuum (2 mBar) for 10 hours at 70 C under solvent-less conditions. LC-MS ToF of reaction products results showed chromatographic peaks for the presence of two new estolide compounds, oleic-oleic monoestolide acid (m/z 563.51, as [M-H]-), and oleic-oleic diestolide acid (m/z 845.77 [M-H]-). The optimum loading of HClO4 for every support are 15 wt.% HClO4/SiO2 (SiO215), 10 wt.% HClO4/SG (SG10) and 35 wt.% HClO4/Al 2O3 (Al2O335). The SG10 turned out to be the best catalyst, achieving a final conversion of 97.5 % with 79.8 % selectivity to oleic-oleic monoestolide acid and 17.7 % selectivity to oleic-oleic diestolide acid. The activity and selectivity of the SG10 have been investigated and compared with homogeneous HClO4. The optimum catalysts for every support were characterized by XPS analysis, BET, TEM and TPD-NH3.